Determining the common medical presenting problems to an accident and emergency department. Issue 5 (1st May 2001) - Armon, K; Stephenson, T; Gabriel, V; MacFaul, R; Eccleston, P; Werneke, U; Smith, S
Abstract : All accident and emergency (A&E) attendances over a one year period were prospectively studied in order to determine common medical presenting problems. Data were collected on children (0–15 years) attending a paediatric A&E department in Nottingham between February 1997 and February 1998. A total of 38 982 children were seen. The diagnoses of 26 756 (69%) were classified as trauma or surgical, and 10 369 (27%) as medical; 1857 (4%) could not be classified. The commonest presenting problems reported for "medical" children were breathing difficulty (31%), febrile illness (20%), diarrhoea with or without vomiting (16%), abdominal pain (6%), seizure (5%), and rash (5%). The most senior doctor seeing these patients in A&E was a senior house officer (intern or junior resident) in 78% of cases, paediatric registrar (senior resident) in 19%, consultant (attending physician) in 1.4%, and "other" in 2.6%. Guidelines developed for A&E should target the commonest presenting problem categories, six of which account for 83% of all medical attendances, and be directed towards senior house officers.